Business Performance Measurement and Management New Contexts, Themes and Challenges - Taticchi, Paolo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Measuring and managing the performance of a business is one of the most genuine desires of management. Balanced scorecard, the performance prism and activity-based management are the most popular frameworks in this setting. Based on the findings of R.G. Eccles$1 (Bacclaimed "Performance Measurement Manifesto (1991)" this book introduces new contexts and themes of application and presents emerging research areas related to business performance measurement and management, e.g. SMEs and sustainability. As a result of the 1st International Summer School Piero Lunghi on "Perspectives of Business Performance Management" this book is written both for students and academics, as well as for practitioners looking for new, yet proven ways to measure and manage business performance.s
What is next by context: PMM in Small and Medium Enterprises -- Performance Measurement and Management in Smes: Discussion of Preliminar Results from an Italian Survey -- New Integrated Information Systems and Management Control Change in Small and Medium Enterprises -- What is next by context: PMM in Collaborative Environments -- A Framework for Evaluating Enterprise Network Performances -- Performance Analysis of Rfid Applications in Cold Chain Management -- What is next by context: PMM in Applications to Special Sectors -- A Performance Measurement System for Racing Teams: An Exploratory Study in an Unresearched Context -- How Small Firms in the High Quality Food Sector Can Improve Their Business Performance: The Ligurian Oil Case Study -- How to Use Different Measures for Different Purposes: A Holistic Performance Management Model for Public Organizations -- What is next by theme: PMM and Sustainability Management -- Using Qualitative System Dynamics to Enhance the Performance Measurement of Sustainability -- Operationalising Sustainability: How Small and Medium Sized Enterprises Translate Social and Environmental Issues into Practice -- Supplier Performance Evaluation for Green Supply Chain Management -- What is next by theme: PMM and Project/HR/Risk Management -- A Synthetic Measure for the Assessment of the Project Performance -- A Project Manager Suitability Parameter in Project Accomplishment -- The Dilemma of Performance Appraisal -- Risk in Supply Networks: The Case of Aeronautical Firms -- What is next by challenge: PMM Models$1 (BEvolution -- A Framework for Performance Measurement and Management Based on Axiomatic Design and Analytical Hierarchy Process -- Designing and Implementing Performance Management Systems -- The Three-Stage Evolution of Full Cost Accounting in Business Economics -- What is next by challenge: PMM Traditional Measurement Cases -- The Measurement System Analysis as a Performance Improvement Catalyst:A Case Study -- Multi-Echelon Inventory Performance Evaluation: The Case of a Communications Company -- Alignment of Strategy-Managerial Characteristics and Performance at the Functional Level in Dubai Local Government -- What is next by challenge: PMM Innovative Way of Measurement -- Understanding Organisational Knowledge-Based Value Creation Dynamics: A Systems Thinking Approach -- Neural Networks and Regressive KPI Metamodels for Business Corporate Management: Methodology and Case Study -- Performance Measurement Systems and Organisational Culture: Interpreting Processes of Unlearning and Change.s
Keywords: Economics; Industrial management; Business planning; Economics/Management Science; Organization/Planning.; Management/Business for Professionals; Business/Management Science, general